2013
DOI: 10.1007/s13404-013-0096-7
|View full text |Cite
|
Sign up to set email alerts
|

Green biosynthesis of gold nanometre scale plates using the leaf extracts from an indigenous Australian plant Eucalyptus macrocarpa

Abstract: In this preliminary study, we demonstrate an environmentally friendly process for the green synthesis of gold nanometre scale particles using the leaf extract from an indigenous Australian plant Eucalyptus macrocarpa as both the stabilising agent and the reducing agent. The synthesis process is straightforward, clean and non-toxic. It also has the advantages of being performed at room temperature and does not need complex processing equipment. Formation of the gold nanometre sized particles was confirmed and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Previous studies report the brown colour indicates the formation of Ag nanoparticles in the reaction mixture due to excitation of surface plasmon vibrations as seen in Figure 1b. 24,26 Mie"s theory predicts a single intense SPR peak in the absorption spectra for spherical metal nanoparticles. However, the broad peak centred at 440 nm in this study was due to the anisotropic nature of the nanoparticles.…”
Section: Scanning Electron Microscopy (Sem) and Energy Dispersive Spementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies report the brown colour indicates the formation of Ag nanoparticles in the reaction mixture due to excitation of surface plasmon vibrations as seen in Figure 1b. 24,26 Mie"s theory predicts a single intense SPR peak in the absorption spectra for spherical metal nanoparticles. However, the broad peak centred at 440 nm in this study was due to the anisotropic nature of the nanoparticles.…”
Section: Scanning Electron Microscopy (Sem) and Energy Dispersive Spementioning
confidence: 99%
“…Biological synthesis was adopted since previous studies by the authors on other Australian indigenous plants have shown that the leaf extracts can act as both reducing agent and stabilizing agent during the synthesis process. 24 Also, the aqueous based technique is straightforward, eco-friendly and produces no toxic waste products.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to avoid the disadvantages associated with traditional manufacturing processes new green chemistrybased procedures using biological entities such as bacteria, fungi, yeast, and plant extracts are currently under investigation. [18][19][20][21] Among the alternatives, the use of plant extracts offers a straight-forward, clean and eco-friendly method of producing noble nanoparticles such as Au and Ag. 22,23 However, very little research has been done investigating the possible utilization of naturally occurring agricultural plant wastes for the biogenic synthesis of Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, size reduction also tends to introduce surface imperfections that can significantly impact the overall physicochemical properties of the fabricated nano particle. The second, bottom up approach builds nanoparticles via the assembly of atoms, molecules, and smaller particles or monomers [11]. Unfortunately, many of the chemical and physical processes used in both approaches suffer from several drawbacks such as low material conversion rates, are technically complex, have high energy requirements, and are generally expensive.…”
Section: Introductionmentioning
confidence: 99%